Moodle quizzes as a teaching tool in English for academic purposes course. (2019) - Amer, Ahmad; Daher, Wajeeh
Moodle is a learning management system (LMS) whose popularity, as adjunct to traditional courses ('blended' or 'hybrid') or as a tool for distance education programs in various disciplines, is rapidly increasing. The research goal was to examine college students' acceptance of this LMS for learning 'English for academic purposes' course (EAP), when Moodle is rich in quizzes. One hundred twenty-nine BEd college students from the two specialisations (special-education and early-childhood) participated in the research. The technology acceptance model was used to examine college students' acceptance of this version of Moodle. The research results demonstrate that the participants rated the experience above average. In addition, the results show that the three components PU, CSE, and PEU are proved key determinants, not only of EAP students' attitudes towards Moodle platform that is rich in quizzes, but also their future use of this platform as academic learners, and thus as teachers. The participants' intrinsic and extrinsic motivations had significant correlations with the five components of Moodle acceptance for EAP.